Propagation of Constraints along Model Transformations Based on Triple Graph Grammars - Ehrig, Hartmut; Hermann, Frank; Schölzel, Hanna; Brandt, Christoph (Electronic Communications of the EASST, 2011)
Model transformations based on triple graph grammars (TGGs) have been applied in several practical case studies and they convince by their intuitive and descriptive way of specifying bidirectional model transformations. Moreover, fundamental properties have been extensively studied including syntactical correctness, completeness, termination and functional behaviour. But up to now, it is an open problem how domain specific properties that are valid for a source model can be preserved along model transformations such that the transformed properties are valid for the derived target model. In this paper, we analyse in the framework of TGGs how to propagate constraints from a source model to an integrated and target model such that, whenever the source model satisfies the source constraint also the integrated and target model satisfy the corresponding integrated and target constraint. In our main new results we show under which conditions this is possible. The case study shows how this result is successfully applied for the propagation of security constraints in enterprise modelling between business and IT models.